Representasi Perempuan Muslim dalam Novel Asma Nadia Periode 2023-2025: Kajian Kritik Sastra Feminis - Diana, Ani; Fitriati, Siti; Tussolekha, Rohmah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to identify patterns of Muslim women’s representation that integrate Islamic spirituality and critical gender consciousness in Asma Nadia’s novels published between 2023 and 2025. Employing a qualitative approach, the research applies content analysis to 127 textual excerpts selected based on four operational criteria: awareness of gender subordination, articulation of agency, Islamic spiritual grounding, and transformative orientation. The findings reveal four major representational dimensions, (1) spirituality as an active empowerment strategy through religious practices that produce concrete impacts; (2) women’s agency in redefining success through the rejection of patriarchal norms grounded in emancipatory theological interpretation; (3) structural resistance through women’s solidarity in humanitarian conflict contexts with transnational dimensions based on ummah identity; and (4) the integration of these dimensions into a spiritual-transformative model of Muslim womanhood. The study demonstrates that religiosity and emancipation are not dichotomous but mutually reinforcing in contemporary Indonesian literary representations.